Numerical Investigation of a New Modified Savonius Wind Turbines - Khalid Mrigua; Mounia Zemamou; Mohammed Aggour (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
The classic Savonius semi-circular blade turbine has a relatively low power coefficient.The performance of a Savonius wind turbine depends on its geometrical parameters. Various blade profiles have been developed in the past years to improve the performance of this class of turbine. In this paper, a new blade shapes of Savonius wind turbine is investigated numerically by using the CFD method , by using transient conditions and set k omega turbulence model.The new blade has different concave and convex shape, which is a combination of the conventional and the elliptical blade. A comparative study of three blade profiles, semi-circular, elliptical and the composed blades have been performed.Flow structures around the rotor have also been analyzed. The results show that changing the blade shape has an effect on the performance efficiency of the Savonius turbine.The new modified and the elliptical blade exhibit higher performance compared to the conventional Savonius wind turbine. The new modified Savonius blade and the elliptical blade exhibit an improved performance compared to the conventional model in the order of 20.5% and 18.2% respectively at the tip speed ratio of 0.8.